EDUCATION OF THE PRAXEOLOGICAL CULTURE OF THE STUDENTS OF AGRARIAN UNIVERSITY IN THE PROCESS OF PROFESSIONAL TRAINING - Oliinyk, Natalia; Bilyk, Tatiana; Komarivska, Nadiia; Imber, Viktoriia; Dabizha, Liudmyla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
On the basis of scientific sources analysis, the characteristic features of praxeological culture of the student at Agrarian University have been revealed. The author has studied the main proceedings which are the basis for the construction of the theoretical foundations of the student’s praxeological culture education. There has been proved that the student’s praxeological culture is determined by the total level of culture of the people who are involved in Pedagogical University activities, their cultural traditions arising from the standards of conduct, their attitudes being expressed in practical actions, in motivations of everyday activity, and their educational strategies.The article describes the rationale for the education of praxeological culture in the process of teaching the discipline "Praxeological culture of a specialist" for students of the specialties «Agronomy», «Management», «Agro engineering». The content of students' training is revealed through the values, principles and technologies of establishing communicative, professional relations in various industrial situations. To achieve this goal, interactive methods and the GROW coach technique were used; for the statistical analysis of the results of experimental work, the Fisher criterion is used. It is shown that experimental exercises and trainings contribute to the effective formation of praxeological culture and professional competence, future specialists of the agro-industrial complex, as evidenced by monitoring and evaluation of the success of training and development of students. According to the results of the experiment, it can be noted that knowledge of praxeological culture will help future specialists to establish contacts in a team, increase mental activity, and increase the level of creativity of young people.